Mobile Crowd Sensing Application for Noise Monitoring in Kuala Lumpur - Zafar, Rashid; Zuhairi, Megat F.; Yafi, Eiad; Dao, Hassan; Salleh, Hilmi M. (International Journal of Engineering and Technology, 2018)
Mobile Crowd Sensing (MCS) technology enables mobile devices, such as smart-phones or other android-based devices that are equipped with embedded sensors to gather relevant data for research work. Typically, the MCS application field ranges from online social-media monitoring, transportation system monitoring, atmosphere monitoring and etc. The inherent attributes of MCS applications is the ability of the system to monitor and collect data over a huge geographical area. Generally, the planners of MCS select participants based upon the scope of survey or the type of data to be acquired. Consequently, based on user’s movement behaviour and location, the MCS application running on the background is able to discreetly collects data from the proximate areas. In principle, this research work highlights the development of MCS application, using the noise parameter as input. The research work shows the feasibility of MCS for data gathering. However, it is essential that data obtained from smartphone’s sensor i.e. microphone is properly processed. Basically, the MCS application is designed to be able to interact with the sensor components within the smartphone. Data is collected and has to be periodically uploaded to the server, where analytical operation is undertaken to produce meaningful information. In principle, the MCS application is able to provide viable noise data in many different areas in Kuala Lumpur. The main benefit that the MCS application can offer is the ability to provide continuous data collection with minimal resource needed.